Analysis of NIK Data Breaches and Their Implications for Achieving the SDGs in Indonesia: A Case Study and Policy Recommendations - Wanasiri, Yunita (Ebiz Prima Nusa, 2025)
The case of NIK (Nomor Induk Kependudukan or Indonesian Identification Number) data breaches in Indonesia highlights the urgent need for robust data protection. These breaches pose a high risk of identity theft, financial fraud, and other cybercrimes, having widespread impacts on society and economic stability. This study compares Indonesia's data protection framework with that of developed countries such as Singapore and South Korea, identifying significant shortcomings in data governance. Through a systematic literature review, this research examines the factors causing NIK data breaches, their social impacts, and the necessary policy recommendations. Key findings include weaknesses in cybersecurity infrastructure, human error, and minimal regulatory oversight, which exacerbate the risk of breaches. The consequences include a decline in public trust, an increase in cybercrime, and economic losses. Proposed policy recommendations include the establishment of an independent data protection authority, strengthening cybersecurity infrastructure, and enhancing education and awareness about data privacy. The NIK data breaches underscore the urgency for Indonesia to strengthen data protection regulations to create a safer and more trustworthy digital environment.